Recent Trends in Correspondent Banking Relationships : Further Considerations. (Policy Papers; Policy Paper ;, 2017)
Correspondent banking relationships (CBRs), which facilitate global trade and economic activity, have been under pressure in several countries. So far, cross-border payments have remained stable and economic activity has been largely unaffected, despite a recent slight decrease in the number of CBRs. However, in a limited number of countries, financial fragilities have been accentuated as their cross-border flows are concentrated through fewer CBRs or maintained through alternative arrangements. These fragilities could undermine affected countries' long-run growth and financial inclusion prospects by increasing costs of financial services and negatively affecting bank ratings.